Stream fish from recently deforested basins in the Meridional Amazon, Mato Grosso, Brazil - Casatti, Lilian [UNESP]; Brejao, Gabriel Lourenco [UNESP]; Carvalho, Fernando Rogerio; Silva, Hugmar Pains da; Perez-Mayorga, Maria Angelica [UNESP]; Manzotti, Angelo Rodrigo [UNESP]; Zeni, Jaquelini de Oliveira [UNESP]; Santos Ramires, Bruno Martins [UNESP]; Langeani, Francisco [UNESP] (Revista Biota Neotropica, 2020)
The replacement of tropical forests to production systems is one of the leading causes of riverine ecosystem alterations. However, current assemblages' composition may also result from the time since these transformations have begun. Therefore, the knowledge of diversified historical scenarios can facilitate the accomplishment of actions that involve the aquatic environments recovery. In this study, an inventory of stream fish was carried out in basins whose deforestation was intensified in the last 20 years, to compose a baseline for ecological and taxonomic studies. The habitat, physical and chemical variables, and the fish assemblages from 60 streams in the northwest region of the state of Mato Grosso, in the Aripuana and Juruena river basins, were sampled with standardized procedures. For a total of 130 species, a numerical predominance of small-sized Characidae and great rarity were registered, with 50 species represented by less than ten individuals and 19 singletons. Approximately 15% of the sampled taxa were identified only at the generic level, and for several taxa, more detailed taxonomic and molecular studies are required in order to achieve satisfactory identifications. None threatened species were so far reported. On the other hand, two specimens of non-native species were sampled. Although habitat quality is higher in forested streams, no differences in the species richness were registered when compared to the pasture with riparian forest streams or to more deforested streams. However, abundance was greater in these last two streams groups as a result of small-sized characins dominance.
Keywords: inventory; neotropical ichthyofauna; deforestation; baseline; Characidae